2018
DOI: 10.1007/s13244-018-0637-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of arterial stroke mimics: a pictorial review

Abstract: Acute ischaemic stroke represents the most common cause of new sudden neurological deficit, but other diseases mimicking stroke happen in about one-third of the cases. Magnetic resonance imaging (MRI) is the best technique to identify those ‘stroke mimics’. In this article, we propose a diagnostic approach of those stroke mimics on MRI according to an algorithm based on diffusion-weighted imaging (DWI), which can be abnormal or normal, followed by the results of other common additional MRI sequences, such as T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 61 publications
1
28
0
2
Order By: Relevance
“…Neuroimaging examinations may demonstrate characteristic findings of HSE and are of great importance in the differential diagnosis. As reported in the literature, 5,11,24 our results also demonstrated that the lesions on conventional MR imaging manifest as an asymmetric involvement of the temporal lobes. Other brain regions, such as frontal lobes, insular lobes, hippocampus region, and cingulate cortex, might also be affected, while the basal ganglia region and cerebellum are rarely involved.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Neuroimaging examinations may demonstrate characteristic findings of HSE and are of great importance in the differential diagnosis. As reported in the literature, 5,11,24 our results also demonstrated that the lesions on conventional MR imaging manifest as an asymmetric involvement of the temporal lobes. Other brain regions, such as frontal lobes, insular lobes, hippocampus region, and cingulate cortex, might also be affected, while the basal ganglia region and cerebellum are rarely involved.…”
Section: Discussionsupporting
confidence: 89%
“…Other brain regions, such as frontal lobes, insular lobes, hippocampus region, and cingulate cortex, might also be affected, while the basal ganglia region and cerebellum are rarely involved. 24 Routine MR images including T1WI, T2WI, T2 FLAIR, DWI, and postcontrast images are most important in identifying brain abnormalities in HSE. Perfusion imaging has been widely applied in research and clinical practice to provide more information in various neurologic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is particularly difficult if it is the first attack of MS. While CT may be normal, MRI will show white matter lesions in typical locations and often additional asymptomatic lesions [ 20 ]. It is important to remember that the event may be an acute stroke in a patient with MS.…”
Section: Common Conditions That Present As Stroke Mimicsmentioning
confidence: 99%
“…Brain lesions with restricted diffusion typically indicate stroke, but given this patient’s presentation, I will consider a broader differential diagnosis. 18 Encephalitic and demyelinating lesions can have restricted diffusion, and demyelination has been reported in association with Covid-19–related encephalitis. 6 , 14 , 19 However, demyelinating lesions are usually patchy and associated with leptomeningeal enhancement and moderate-to-severe respiratory illness, characteristics that are not consistent with those seen in this patient.…”
Section: Differential Diagnosismentioning
confidence: 99%